Reflections on the current threats to democracy - Forsyth, Harold (2022)
Rising expectations, unfulfilled electoral promises, the weariness of political discourses, the persistent corruption in varying degrees of publicand private activity, the polarization of political discourses, among other factors, have been eroding the legitimacy of democracies and have allowed the expansion of intolerant and authoritarian discourses, as well as have cultivated practices that tend to restrict rights. We highlight some reflections on the most visible threats facing democratic regimes, after briefly addressing some fundamental concepts about the notion of democracy and governance.